Structural and functional features of healing of tiba fractures using apiphonophoresis - A. Gozhenko; K. Pavlenko; V. Chivga (Journal of Education, Health and Sport)
Modernity is defined as an "epidemic of trauma". Every year, up to 2 million adults and 300 thousand children, residents of Ukraine, receive various injuries. Since injuries and their consequences are the cause of disability in 89% of the working population, the problem of trauma, including bone fractures, becomes not only a medical but also a social problem. In this regard, the treatment of injuries in general and fractures in particular remains very relevant.